Ambiguity towards Multiple Historical Performance Information Signals: Evidence from Indonesian Open-Ended Mutual Fund Investors - Loeis, Haris Pratama; Prijadi, Ruslan (The Indonesian Capital Market Review, 2015)
This study focuses on the behavior of open-ended mutual fund investors when encountered with multiple information signals of mutual fund’s historical performance. The behavior of investors can be reflected on their decision to subscribe or redeem their funds from mutual funds. Moreover, we observe the presence of ambiguity within investors due to multiple information signals, and also their reaction towards it. Our finding shows that open-ended mutual fund investors do not only have sensitivity towards past performance information signals, but also have additional sensitivity towards the ambiguity of multiple information signals. Because of the presence of ambiguity, investors give more consideration to negative information signals and the worst information signal in their investment decisions.